Translation techniques of swear words in "After We Collided by Roger Kumbler - Wati, Intan Adelia Rhmah; Larassati, Anisa (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
This research aims to find out the types of swear words, translation techniques, and the changes in meaning in the After We Collided movie. A descriptive-qualitative approach is used in this research. Based on the findings and discussion, there were 50 data on swear words and translation techniques. Shift in meaning, as many as 16 data had found. There are 4 types of swear words: abusive (42%), cathartic (30%), idiomatic (24%), and emphatic (4%). There are 6 translation techniques used: adaptation (60%), amplification (4%), reduction (20%), modulation (2%), established equivalence (6%), and literal translation (8%). Shift in the meaning of eufimia as many as 12 data are found in 4 translation techniques: reduction, adaptation, modulation, and amplification. Loss of information as many as 4 data found in reduction techniques. The reason why abusive swearing becomes the most frequently found data is because it shows the use of language intended to harass, intimidate, and humiliate the interlocutor. The adaptation technique is the most used because swear words are translated with equivalents that are often used in Indonesian culture. Eufimia found in this data because swear words in the target language become more refined. Loss of information occurs when words in the source language are not translated into the target language.